Reforming the legislation of the Republic of Kazakhstan on the labor law liability of medical and pharmaceutical workers in the context of international standards and best foreign practices - Khassenov, M.Kh. (Bulletin of the Karaganda University “Law Series”, 2022)
This article presents the results of a study of the institution of labor law liability of medical and pharmaceutical workers to develop and justify recommendations for reforming the legislation of the Republic of Kazakhstan. The author used general scientific (analysis and synthesis, deduction and induction) and private scientific research methods (comparative legal, formal legal, legal modeling) to achieve the goal and ensure the reliability of the obtained results. The article provides an analysis of the legal personality, the current state of the legislative framework and law enforcement of the institution of labor and legal liability of medical and pharmaceutical workers in Kazakhstan, a comparative legal analysis of the legislation and law enforcement of a number of foreign countries. The article substantiates the need to introduce independent regulation of the disciplinary and material liability of medical and pharmaceutical workers, by analogy with the best world practice, by establishing a unified procedure and bodies for considering relevant situations in special legislative acts and procedures. It is proposed to remove from the competence of employers the issue of bringing medical and pharmaceutical workers to disciplinary liability for committing disciplinary offenses related to their professional activities concerning patients, as well as issues and bringing them to liability for damage caused to the employer. Relevant situations should be considered centrally by specially created independent bodies — medical boards in each region (oblast, city of republican significance and the capital) to ensure objectivity, impartiality, and uniformity in the use of relevant standards and regulations, as well as professional ethics. These measures will improve the status of medical and pharmaceutical workers, streamline the issues of liability in labor relations, reduce the risks of abuse by employers and ensure the widespread implementation of internationally recognized standards and best foreign practices in disciplinary proceedings and the resolution of disputes on liability involving representatives of the medical and pharmaceutical professions.